Philosophy of Economics : On the Scope of Reason in Economic Inquiry. - Roy, Subroto (International library of philosophy., 1991)
The first work to seriously and successfully bridge twentieth century economics and twentieth century philosophy. Subroto Roy draws these two disciplines together and examines the basic intellectual roots of economics.